Variations in headspace microextraction procedures and current applications in bioanalysis. (September 2015) - Gonçalves, Alexandra; Gallardo, Eugenia; Barroso, Mário
In sample preparation, analytes are extracted from the sample and concentrated in a solvent compatible with analytical instrumentation. Some drawbacks are usually associated with the procedures traditionally used, namely the amounts of organic solvents that need to be properly discarded and the presence of several interferences which may impair analyte identification and quantitation. Headspace microextraction procedures have appeared as a promising solution to overcome these problems. On the one hand, being microextraction techniques, the amount of solvent and sample is reduced; on the other hand, since it is the headspace above the specimen which is sampled rather than the sample itself, analytical interferences are minimized, prolonging the lifetime of the devices and analytical instrumentation.